Controle distribuído de tráfego baseado em veículos conectados - Gonçalves, Fabrício Barros (2017)
Although advanced traffic management systems can deal with the heterogeneous traffic flows approaching of intersections, their performances are compromised, when the traffic volume is not distributed uniformly. To evenly distribute the traffic flow, an advanced driver information system should be aware of the traffic control operations. However, such requirement can not ultimately be satisfied due to the gaps in state of the art in advanced traffic management systems. Therefore, this study proposes a distributed traffic control system, in which agents embedded in connected vehicles, traffic signals, urban elements and a traffic control center interact with each other to provide a greater traffic fluidity. Therefore, the agents depend strongly on a heterogeneous vehicular network. In this sense, this study also proposes a heterogeneous vehicular network whose communication protocol can satisfy the communication requirements of intelligent transportation systems service applications. According to the results obtained from simulations, the distributed traffic control system was able to maximize the flow of vehicles and the mean speed of the vehicles, and minimize the wait time, travel time, fuel consume and emissions (CO, CO2, HC, NOx and PMx).